PENINGKATAN MOTIVASI DAN HASIL BELAJAR PECAHAN DENGAN MENGGUNAKAN PENDEKATAN KOOPERATIF TIPE TGT DI KELAS V SDN 04 KAYU MANANG - Saidi Saidi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
The research was motivated by the low motivation and learning outcomes of mathematics in class V SDN 04 Kayu Manang Surian. The research objective is to increase motivation and learning outcomes of Mathematics by using the approach of cooperative type of TGT. This type of research is Classroom Action Research, which was carried out in 2 cycles in the second semester of 2015/2016 with the subject of teacher research and fifth grade students totaling 22 people. Research data were collected through observing student activities, learning motivation questionnaires and tests. The research findings show that the use of the TGT cooperative model approach can increase motivation and student learning outcomes in learning mathematics. Increased student motivation can be seen in the first cycle with a percentage of 20% of students expressed strongly agree, 51% of students agreed. Whereas in the second cycle, they got a score of 46%, the students strongly agreed, 30% of the students agreed. Improved student learning outcomes seen in cycle 1 with an average value of 68.55, in the second cycle to 7.32. Based on the findings of this study concluded that the approach model of learning cooperative tpe TGT can be used as an alternative to increase motivation and student learning outcomes in learning mathematics